Risk of morbidity and mortality in patients with type 2 diabetes treated with sodium-glucose cotransporter-2 inhibitor and/or dipeptidyl peptidase-4 inhibitor: a nationwide study - Gyula Poór; Gábor Sütő; Gergő A Molnár; Gyorgy Rokszin; Ibolya Fábián; Zoltan Kiss; György Jermendy; Peter Kempler; István Wittmann (BMJ Open Diabetes Research & Care)
Introduction Mortality and disability in diabetes mellitus are determined mostly by cardiovascular complications and cancer. The impact of dipeptidyl peptidase-4 inhibitor (DPP-4i) and sodium-glucose cotransporter-2 inhibitor (SGLT2i) monotherapy or combination on long-term complications of type 2 diabetes mellitus was studied.Research design and methods Patients with type 2 diabetes treated with DPP-4i or SGLT2i during a 3-year period were identified in the database of the National Institute of Health Insurance Fund in Hungary. All-cause mortality, acute myocardial infarction, stroke, hospitalization for heart failure (HHF), lower limb amputation (LLA) and cancer were assessed. Outcomes of add-on SGLT2i to DPP-4i treatment in comparison with switching DPP-4i therapy to SGLT2i were also evaluated. After propensity score matching, survival analysis was performed with a Cox proportional hazards model.Results After propensity score matching, both SGLT2i and DPP-4i groups included 18 583 patients. All-cause mortality (HR, 0.80; 95% CI 0.68 to 0.94; p=0.0057), HHF (HR, 0.81; 95% CI 0.71 to 0.92; p=0.0018), and risk of cancer (HR, 0.75; 95% CI 0.66 to 0.86; p<0.0001) were lower in the SGLT2i population compared with DPP-4i. Risk of LLA was higher in the SGLT2i group (HR, 1.35; 95% CI 1.03 to 1.77; p=0.0315). SGLT2i in combination with DPP-4i results in lower all-cause mortality (HR, 0.46; 95% CI 0.31 to 0.67; p=0.0001), with a lower trend in stroke, LLA, HHF and cancer, but without any statistical difference.Conclusions SGLT2i treatment leads to a lower risk of overall mortality, HHF and cancer when compared with DPP-4i treatment. Adding SGLT2i to DPP-4i instead of switching from DPP-4i to SGLT2i further lowers the risk of all-cause mortality.